1989
DOI: 10.1128/aem.55.11.2793-2797.1989
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria of Cotton and Their Repression of Seedling Disease Pathogens

Abstract: During the 1983 field season, the rhizobacteria (including organisms from rhizosphere soil and the root rhizoplane) of cotton plants at one location in Mississippi were inventoried at different plant growth stages. Isolates (1,000) were identified to the genus level and characterized for repression of Pythium ultimum and Rhizoctonia solani. Cotton seedlings were initially colonized by bacteria of many different genera, and populations quickly reached 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The antifungal activity of rhizobacteria has been ascribed to these bacterial groups by many authors (e.g. [7,43,44]). Of the Streptomyces isolates from spruce humus 46% suppressed one or more of the indicator fungi, similar to the frequency reported previously for rhizosphere and non-rhizosphere isolates [7,44].…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of rhizobacteria has been ascribed to these bacterial groups by many authors (e.g. [7,43,44]). Of the Streptomyces isolates from spruce humus 46% suppressed one or more of the indicator fungi, similar to the frequency reported previously for rhizosphere and non-rhizosphere isolates [7,44].…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of rhizobacteria has been ascribed to these bacterial groups by many authors (e.g. [7,43,44]). Of the Streptomyces isolates from spruce humus 46% suppressed one or more of the indicator fungi, similar to the frequency reported previously for rhizosphere and non‐rhizosphere isolates [7,44].…”
Section: Discussionmentioning
confidence: 99%
“…The humus bacteria may thus have natural potential for attenuating autochthonous fungi as biological control agents in spruce nurseries. Several reports indicate a correlation between in vitro growth inhibition and biocontrol [45], but many other studies found no advantage in screening the strains in vitro [43–45]. Broadbent et al [46] noted that strains nonantagonistic in plate assays were generally inactive in soil also.…”
Section: Discussionmentioning
confidence: 99%
“…Plates were incubated at 20°C for five days and examined for the evidence if the growth of the fungus was inhibited by the bacteria. A positive response was any visible zone of inhibition around the fungus, regardless of the size of the zone (Hagedorn et al, 1989). All the 47 bacterial isolates were tested in three independent replicates.…”
Section: Antifungal Activitymentioning
confidence: 99%